The role of local government in the local autonomy framework in the implementation of REDD+ in Indonesia / Dian Agung Wicaksono and Wahyu Yun Santosa - Wicaksono, Dian Agung; Yun Santosa, Wahyu (Faculty of Administrative Science and Policy Studies, 2012)
The world is racing to fight deforestation and forest degradation amidst the effort to reduce emission to mitigate climate change. REDD+ offers a new and more effective approach because it provides financial incentives for forest carbon storage. This approach is evidently different from the conventional forest conservation efforts. Simple, it might look. However, the practical implementation of REDD+ has proven to be cumbersome. In the context of Indonesia and its local autonomy policy, REDD+ presents both prospects and challenges. This study attempts to analyse the role of local government in the local autonomy framework in the implementation of REDD+. This study is a normative-juridical research using literature review to dissect secondary data. Among the secondary data that this study has dissected are statutory regulations, various legal documents, past studies, and other references which are relevant with the role of local government in the implementation of REDD+ in Indonesia, under the context of local autonomy. Indonesia has seen the implementation of REDD+ inherently laden with prospects and challenges. On the one hand, REDD+ can empower communities living in and surrounding forests and can provide simultaneous forest preservation. On another hand, problem in sectoral regulations present considerable challenges. Consequently, a working strategy and design to adjust REDD+ implementation to Indonesia’s nature as a decentralized unitary state is needed.